Efficient method for tetrahydropyranylation/depyranylation of phenols and alcohols using a solid acid catalyst with Wells-Dawson structure - Romanelli, Gustavo Pablo (2002)
A simple and efficient procedure to form 2-tetrahydropyranyl acetals of phenols and alcohols is reported. Wells-Dawson heteropolyacid catalyst is used both in bulk form or supported on silica, reaction conditions include room temperature and toluene as solvent. Fast deprotection of THP-acetals can be attained by mere change of the solvent using THF-1% MeOH. In both reactions the supported catalyst is easily recoverable and reusable, and the yields are good to excellent. © 2002 Elsevier Science Ltd. All rights reserved.